Structural, geochemical and host rock control on gold mineralization in tholeiitic volcanic rock of the Tisdale assemblage, Timmins, Ontario; the Hoyle Pond mine and the Vipond V10b unit - Dinel, Etienne (University of Ottawa (Canada), 2007)
The Hoyle Pond mine is located 15 km northeast of the city of Timmins, Ontario, in the Porcupine Gold Camp. It is hosted in deformed mafic to ultramafic volcanic rocks of the Tisdale assemblage. Geochemical data and structural analyses show interesting relations between host rock control and mineralization. The Au-bearing quartz-carbonate veins of the Hoyle Pond mine are hosted in a south-facing homoclinal sequence of stacked meta-volcanic rocks that are concordant with the Hershey Lake and Central formations of the Tisdale assemblage. The rocks were subjected to numerous sub-greenschist metamorphic events; however, detailed mapping shows that the hydrothermal mineralization took place during D3 and D4 events, and was associated with isoclinal folding, shearing, and thrusting. The alteration associated with the gold mineralization consists of a sericite alteration, which is immediately enveloped by an albite alteration zone. The inner alteration zone is composed of sericite, Cr-mica "fuchsite", quartz, Fe-dolomite, arsenopyrite, pyrite, tourmaline and graphite, and has a concomitant enrichment in K2O, Cr, SiO2, CO2 , As, and S. The albite alteration zone is composed of albite, quartz and Fe-dolomite, and has an enrichment in Na2O, CO2 and SiO2. In addition, carbon enrichment is also associated with mineralization. A pervasive graphite alteration envelopes the mineralization, and is the result of the oxidation of organic matter associated with Au mineralization. Rare Earth elements, Al2O3, Zr, TiO2 and Y were relatively immobile with respect to alteration and can be used to identify rock type. However, K2O, Na2O, Cr2O 3, Rb, CO2, CaO, Eu, FeO, MgO and to a lesser extent La (LREE), were mobile during alteration. Fluid mixing occurred between oxidizing fluids with soluble Cr 6+ and other elements (e.g. K and Na), and reducing fluids carrying gold as a thiol-organic complex (Au-HSCxHx), and other species, (e.g. B and As). The most plausible source of Au, As and B were the meta-sedimentary rocks of the surrounding Porcupine assemblage, whereas the Cr was likely derived from the ultramafic and mafic volcanic rocks. Two generations of fault-fill veins are present at Hoyle Pond: those hosted in D3 structures at lithological contacts, and those associated with D4 structures and located at flow contacts and also on both limbs of isoclinal folds. Due to the intensity of alteration and deformation of the Tisdale assemblage rocks at Hoyle Pond, it remains an open question as to whether the permeability for the mineralization at flow contacts was primary in nature, the result of mechanical contrasts during deformation, or both. The V10b or "chickenfeed" unit of the Tisdale Assemblage hosted significant gold mineralization, and was formerly thought to be composed of pillow basalt. Detailed mapping and geochemical work demonstrate that it is a pillow-lobe dacite of the tholeiitic suite associated with abundant hyaloclastite. The unit had a high intrinsic permeability, competency and Fe/Mg ratio malting it an ideal host for gold. At a regional scale there are two types of Au deposits associated with tholeiitic volcanic rocks: Those hosted in mafic rocks in which C may be important in precipitating gold from hydrothermal solution, and those hosted in more felsic rocks wherein the high Fe/Mg stabilizes the formation of Au scavenging pyrite.
Keywords: Geology.; Geochemistry.